Tipologi pengembangan kawasan berbasis transit di kawasan Stasiun Maguwo, Yogyakarta - Agus Setiawan; Ikaputra (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Transit oriented development (TOD) typology in Maguwo train station area, Yogyakarta Transit oriented development (TOD) is a concept to address problems related to the lack of public transportation use in urban areas. Empirical conditions in Maguwo station area have not applied the TOD principle, especially related to density and diversity aspects, which results in the low intensity of public transportation use, based on these conditions it is necessary to reposition the area with TOD concept. Repositioning Maguwo station area with TOD concept begins with a review of existing conditions and TOD typologies that ideal to be implied in Maguwo station area, finding gaps between existing conditions and ideal TOD typology, and recommendations for resolving the gaps, will be input for design process of TOD area. The study uses quantitative and qualitative deductive methods with research variables including character of regional development, variety, and intensity of spatial use. The research showed the ideal TOD typology applied in Maguwo station area was a sub urban TOD. The gap between the existing conditions and sub urban TOD standard is the lack of residential units and the low intensity of spatial use including building, residential, and population density. Therefore, the design area need to add the number of residential units and increase the intensity of building density to match the sub urban TOD standard. © 2020 Agus Setiawan, Ikaputra